2017
DOI: 10.1097/icl.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Subtenon Injections of Ranibizumab Arrest Growth in Early Recurrent Pterygium

Abstract: In half of the subjects, subtenon ranibizumab appeared to arrest growth. Although the response is variable, this may warrant the drug's use when attempting to control growth of recurrent pterygia, and may prevent consecutive surgery for some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 84 89 Therefore, in recent years, anti-VEGF agents such as bevacizumab and ranibizumab have been studied widely in primary and recurrent pterygium treatment as adjunctive therapy to surgical excision or as a nonsurgical treatment alone. 58 85 86 87 88 89 90 91 92 93 Different routes and doses of administration have been evaluated in multiple studies. Subconjunctival and topical application are the most popular administration techniques.…”
Section: R Esultsmentioning
confidence: 99%
“… 84 89 Therefore, in recent years, anti-VEGF agents such as bevacizumab and ranibizumab have been studied widely in primary and recurrent pterygium treatment as adjunctive therapy to surgical excision or as a nonsurgical treatment alone. 58 85 86 87 88 89 90 91 92 93 Different routes and doses of administration have been evaluated in multiple studies. Subconjunctival and topical application are the most popular administration techniques.…”
Section: R Esultsmentioning
confidence: 99%
“… 3 , 4 More aggressive pterygia are sometimes targeted with 5-FU and subconjunctival anti-VEGF, though these treatments are less proven. 5 , 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…5 , 6 More recent studies, however, have concluded that anti-VEGF injections, particularly subtenon ranibizumab, may have therapeutic utility in pterygium treatment, effectively preventing regression in up to 50% of cases. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rate is with varying rates from 25% to 90% in just excision without covering the conjunctival defect. Therefore, using augmented drugs [e.g., Mitomycin-C, 5-fluorouracil, bevacizumab [5] , ranibizumab [6] , aflibercept [7] , cyclosporine A [8] and interferon α2b [9] ] or other techniques with the covering of the bare area is mandatory [10] .…”
Section: Introductionmentioning
confidence: 99%